Screening for stress-resistance mutations in the mouse - Chick, Wallace S.; Ludwig, Michael; Zhao, Xiaoyun; Kitzenberg, David; Williams, Kristina; Johnson, Thomas E. (Frontiers in Genetics, 2014)
Longevity is correlated with stress resistance in many animal models. However, previous efforts through the boosting of the antioxidant defense system did not extend life span, suggesting that longevity related stress resistance is mediated by other uncharacterized pathways. We have developed a high-throughput platform for screening and rapid identification of novel genetic mutants in the mouse that are stress-resistant. Selection for resistance to stressors occurs in mutagenized mouse embryonic stem (ES) cells, which are carefully treated so as to maintain pluripotency for mouse production. Initial characterization of these mutant ES cells revealed mutations in Pigl, Tiam1, and Rffl, among others. These genes are implicated in glycosylphosphatidylinositol biosynthesis, NADPH oxidase function, and inflammation. These mutants: (1) are resistant to two different oxidative stressors, paraquat and the omission of 2-mercaptoethanol, (2) have reduced levels of endogenous reactive oxygen species (ROS), (3) are capable of generating live mice, and (4) transmit the stress resistance phenotype to the mice. This strategy offers an efficient way to select for new mutants expressing a stress resistance phenotype, to rapidly identify the causative genes, and to develop mice for in vivo studies.